Admission Glucose and Effect of Intra-Arterial Treatment in Patients With Acute Ischemic Stroke. Issue 5 (May 2017) - Osei, Elizabeth; den Hertog, Heleen M.; Berkhemer, Olvert A.; Fransen, Puck S.S.; Roos, Yvo B.W.E.M.; Beumer, Debbie; van Oostenbrugge, Robert J.; Schonewille, Wouter J.; Boiten, Jelis; Zandbergen, Adrienne A.M.; Koudstaal, Peter J.; Dippel, Diederik W.J.
Abstract : Background and Purpose—: Hyperglycemia on admission is common after ischemic stroke. It is associated with unfavorable outcome after treatment with intravenous thrombolysis and after intra-arterial treatment. Whether hyperglycemia influences the effect of reperfusion treatment is unknown. We assessed whether increased admission serum glucose modifies the effect of intra-arterial treatment in patients with acute ischemic stroke. Methods—: We used data from the MR CLEAN (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands). Hyperglycemia was defined as admission serum glucose >7.8 mmol/L. The primary outcome measure was the adjusted common odds ratio for a shift in the direction of a better outcome on the modified Rankin Scale at 90 days, estimated with ordinal logistic regression. Secondary outcome variable was symptomatic intracranial hemorrhage. We assessed treatment effect modification of hyperglycemia and admission serum glucose levels with multiplicative interaction factors and adjusted for prognostic variables. Results—: Four hundred eighty-seven patients were included. Mean admission serum glucose was 7.2 mmol/L (SD, 2.2). Fifty-seven of 226 patients (25%) randomized to intra-arterial treatment were hyperglycemic compared with 61 of 261 patients (23%) in the control group. The interaction of either hyperglycemia or admission serum glucose levels and treatment effect on modified Rankin Scale scores was not significant ( P =0.67 and P =0.87, respectively). The same applied for occurrence of symptomatic hemorrhage ( P =0.39 for hyperglycemia, P =0.39 for admission serum glucose). Conclusions—: We found no evidence for effect modification of intra-arterial treatment by admission serum glucose in patients with acute ischemic stroke. Clinical Trial Registration—: URL:www.isrctn.com . Unique identifier: ISRCTN10888758. Abstract : Supplemental Digital Content is available in the text.